Fabricação e caracterização de dispositivos eletroluminescentes produzidos com compósitos - Feres, Flávio Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Soluble electronic materials have been intensively investigated in the past few years. Their solution processability, combined with specific electronic properties have made them candidates for large areas and low cost electronic devices. Additionally, composites comprising an organic polymeric conductive blend and an inorganic electroluminescent material, which can be processed by liquid route, have been employed as active material in light-emitting devices. Recently, was proposed a new light-emitting composite, which becomes non-soluble after processing by liquid route, comprising the conducting polymer poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), the ORMOSIL material 3-glicidoxypropyltrimethoxysilane (GPTMS) and the inorganic light-emitting powder of Mn-doped zinc silicate (Zn2SiO4:Mn). In the present study, the electro optical properties of light-emitting devices produced with composites comprising different weight fractions of PEDOT:PSS, GPTMS and Zn2SiO4:Mn were evaluated. The different light-emitting composites were coated over glass substrates containing ITO electrodes by drop-casting method and gold top electrodes were produced by thermal evaporation. The device produced with the composite (9.5/0.5/90 %-wt) showed the best performance with turnon voltages 33 V and 2.10³cd/m2 (at 300 V) with luminous efficacy of 24 cd/A. Additionally, were produced and characterized devices with different active layer thickness. Devices produced with active layer thickness on the range 100 μm to 150 μm, exhibited the best performance, with luminance of 103 cd⁄m² at 300 V. The devices turnon voltage have been obtained as proportional to the active layer thickness, indicating that the electroluminescence in the light-emitting devices occurs by a field effect mechanism turned on at electric fields with magnitudes of kV/cm order. Finally, the dependence of the electro optical properties of the devices on the temperatures was...

Materiais eletrônicos solúveis vêm sendo estudados com intensidade nos últimos anos. O processamento rápido em solução, combinado com certas propriedades eletrônicas específicas os tornam grandes candidatos para produção de dispositivos eletrônicos de baixo custo. Adicionalmente, compósitos contendo uma blenda polimérica orgânica condutora e um material inorgânico eletroluminescente que podem ser processados por rota liquida, foram utilizados para a produção de um material ativo em um dispositivo eletroluminescente. Recentemente, foi proposto um novo compósito emissor de luz, que se torna insolúvel após processamento por rota líquida, esse compósito é composto por um polímero condutor (PEDOT:PSS), um material ORMOSIL (GPTMS) e o pó inorgânico emissor de luz silicato de zinco dopado com Manganês (Zn2SiO4:Mn). No presente estudo, as propriedades dos dispositivos emissores de luz obtidos com tal compósito contendo diferentes frações em massa de PEDOT:PSS, GPTMS e Zn2SiO4:Mn foram avaliadas. Os diferentes compósitos emissores de luz propostos foram depositados via drop-casting sobre um substrato de vidro contendo eletrodos de ITO, sobre o compósito foram depositados eletrodos de ouro via evaporação térmica. O dispositivo produzido com compósito (9.5/0.5/90 %-wt) apresentou o melhor desempenho com tensão de operação de 33 V e 2.10³ cd/m² (a 300 V) e eficácia luminosa de 24 cd/A. Adicionalmente, foram produzidos dispositivos com diferentes espessuras de camada ativa. A faixa ótima de espessura foi determinada entre 100 μm e 150 μm, onde a luminância dos dispositivos alcançaram uma magnitude de 103 cd/m² a 300 V. Além disso, foi verificado que a tensão de operação dos dispositivos é proporcional à espessura da camada ativa, indicando que a eletroluminescência dos dispositivos é ocasionada por um mecanismo de efeito de campo, onde o campo elétrico de operação foi determinado da ordem de kV/cm...
Keywords: Polímeros; Eletroluminescencia; Compósitos poliméricos; Condutores organicos; Polimeros condutores; Silicatos; Zinco; Manganes; Eletrodos